Mucoadhesive film containing α-mangostin shows potential role in oral cancer treatment - Piyawat Tangsuksan; Jureeporn Chuerduangphui; Chutha Takahashi Yupanqui; Teerapol Srichana; Ekarat Hitakomate; Chamsai Pientong; Tipaya Ekalaksananan; Wipawee Nittayananta (BMC, 2021)
Abstract Background Oral cancer is often preceded by a mucosal lesion called an oral potentially malignant disorder (OPMD). Many plant-derived compounds are of value in medicine. The objectives of this study were to develop a soluble mucoadhesive film containing α-mangostin (α-MG), a compound extracted from the peel of mangosteen fruit, and determine its activities against oral cancer cells, against human papillomavirus type 16 (HPV-16) pseudovirus, and its anti-inflammatory properties. Methods A soluble mucoadhesive film containing α-MG was prepared. Oral squamous carcinoma cell line (SCC25), murine macrophage cells (RAW264.7), and human gingival fibroblast cell line were cultured. Anticancer activity and viability of SCC25 cells in response to α-MG film solution were determined by MTT assay. HPV-16 pseudovirus was constructed and effects of the film solution on attachment and post-attachment steps of the infection were investigated. Anti-inflammatory activity was assessed by nitric oxide (NO) inhibition. Fibroblast cell migration was determined by in vitro scratch assay. Results The soluble α-MG film showed cytotoxic effects on SCC25 cells in concentration > 125 µg/ml with IC50 of 152.5 µg/ml. Antiviral activity against HPV-16 pseudovirus was observed at attachment step, but not at post-attachment step. The film also possessed a strong anti-inflammatory effect and promoted wound healing without cytotoxicity. Conclusions Mucoadhesive film containing α-MG has a cytotoxic effect on oral squamous carcinoma cell line and an inhibitory effect on HPV-16 pseudovirus at attachment step. The α-MG film also shows a potent anti-inflammatory activity and enhances wound healing. Thus, the soluble α-MG film may have a potential role in treating oral cancer.